REINTERPRETASI SURAT AL-FIIL DALAM KONTEKS WABAH - Ghozali, Mahbub; Dewi, Chandra Kartika (UIN Raden Mas Said Surakarta, 2020)
This study aims at rereading the interpretation of sura (chapter) Al-Fiil with a historical approach. The context of this sura is the incident of the attack of the elephant army led by Abrahah to Makkah. This event coincided with the outbreak of the Justinian Plagueepidemic in Ethiopia. Thus, it is necessary to reread this surawith consideration to the pandemic. This study concludes that certain terms in the suraAl-Fiil represent the events of the pandemic that caused the destruction of Abrahah’s army. Thayr, ababil, and sijjilbecome key terms whose meaning could refer to the cause, spread, and media of the outbreak contracting Abrahah and his army. In addition, a multidisciplinary approach in the interpretation of sura Al-Fiil can support the argument of the miracles of the Qur’an often attributed to the meaning of this suraby some classical interpreters. Similarly, the evidence for the miracles of the Qur’an resulted from this study might reinforce the existence of tafsir bi al-‘ilm.